Application of absorption of infra-red radiation and reflection spectra to distinguish different inks of same color in alteration - Giri, Roshan; Chimouriya, Shanker Prasad; Ghimire, Bal Ram (BIBECHANA, 2022)
The main aim of this study is to introduce non-destructive method to distinguish different types of ink of same color. In our daily life, we face many problems of alteration of genuine documents. Such alteration is done by using same color of ink as used in the document. It is not possible to differentiate the altered part by our naked eyes. There are many methods, destructive as well as non-destructive methods, to solve the problem of alteration. We have discussed the non-destructive method using Video Spectral Comparator (VSC)-6000. Analysis is carried out with application of infra-red (IR) radiation of different wavelength and reflection spectra to reach the conclusion. Absorption of infra-red (IR) radiation is found very effective whereas use of reflection spectra is totally failed in this experiment.BIBECHANA 19  (2022) 34-39